The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/978-3-319-42324-1_24
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Affective Touch: Using a Vibrotactile Array to Generate Pleasant Stroking Sensations

Abstract: Gentle stroking touches are rated most pleasant when applied at a velocity of between 1-10 cm/s. Such touches are considered highly relevant in social interactions. Here, we investigate whether stroking sensations generated by a vibrotactile array can produce similar pleasantness responses, with the ultimate goal of using this type of haptic display in technology mediated social touch. A study was conducted in which participants received vibrotactile stroking stimuli of different velocities and intensities, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…This was based on CT afferent properties discovered from microneurography studies (Nordin, ; Vallbo et al, ). Furthermore, the velocities selected were also those established from investigations of CT afferents in the forearm (Ackerley, Carlsson, et al, ; Croy et al, ; Hielscher & Mahar, ; Huisman, Frederiks, vanErp, & Heylen, ; Jönsson et al, ; Kass‐Iliyya et al, ) and face (Ackerley, Carlsson, et al, ). The findings from the present study complement CT afferent research.…”
Section: Discussionmentioning
confidence: 99%
“…This was based on CT afferent properties discovered from microneurography studies (Nordin, ; Vallbo et al, ). Furthermore, the velocities selected were also those established from investigations of CT afferents in the forearm (Ackerley, Carlsson, et al, ; Croy et al, ; Hielscher & Mahar, ; Huisman, Frederiks, vanErp, & Heylen, ; Jönsson et al, ; Kass‐Iliyya et al, ) and face (Ackerley, Carlsson, et al, ). The findings from the present study complement CT afferent research.…”
Section: Discussionmentioning
confidence: 99%
“…1 Emerging research includes remote, prosthetic and multi-modal interfaces for touch practices between humans, virtual agents, robots (Van Erp and Toet 2015, Huisman 2017). 2 Research on experience of affective touch using vibro-tactile technologies showed that telematic, haptic experiences of slow (1-10 cm/s) gentle stroking of the body, such as caressing, are associated by participants with experiences of affection (Huisman et al 2016). 3 These works can be related to the facial illusion experiment, in which acts of touching a participant's face are mirrored real-time in acts of touching other peoples' faces, visible on a monitor in front of the participant.…”
Section: Related Workmentioning
confidence: 99%
“…We demonstrate the use of tactile interactions across different devices, by detecting static and dynamic touches on a touch-screen based mobile device and a novel wearable touch-sensor. These touches are synthesized on a linear array of vibration motors using phantom haptic sensations [1,12,11]. Our method demonstrates that different input methods can be used for generating similar vibrotactile sensations.…”
Section: Discussionmentioning
confidence: 99%
“…In this demo we introduce a method for the detection and generation of touches, including stroking touches. An optimized method for rendering vibrotactile stroking touches based on the work of [1,12,11,13] is used as output. A linear array of four Precision Microdrives PicoVibe 306-117 vibration motors is worn on the forearm to apply vibrotactile stimulation (see Figure 1).…”
Section: Demo Outlinementioning
confidence: 99%